Profit Theory and Capitalism - Obrinsky, Mark, 1950- (Book collections on Project MUSE., 1983)
The pursuit of profit by business motivates the capitalist economic system. Understanding profits, therefore, especially the source of profits, is essential to an understanding of capitalism. Mark Obrinsky claims that there has never been an adequate profit theory in mainstream economics. To find the source of profits, he argues, one needs to look beyond ownership of the productive factors of land, labor, and capital.Profit Theory and Capitalism makes a sharply reasoned and accessible contribution to critical theory, the history of economic thought, and post-Keynesian theory. Its insights will be of value to all students and theorists working in the area of income distribution.